Socioeconomic conditions of the family in supporting the distance learning process during the Covid-19 pandemic - Laelani Jhofiroh; Yanto Sucahyanto; Aris Munandar; OS Hardi; Samadi Samadi; Cahyadi Setiawan (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The impact of Covid-19 does not only occur in the health sector, but also on other sectors such as social, economic, environmental and even geopolitical and including the education sector. Family socioeconomic conditions have an important role in distance learning process which is carried out during a pandemic so that this research aims toanalyze the family's economic condition of the distance learning process (PJJ) during the Covid-19 pandemic in Cibodas Jonggol Village, West Java. This type of research is quantitative research with a survey approach. The research sample from this study was a family that had family members who were still attending elementary school in Cibodas Village with a total sample of 82 respondents. The research instrument used is an interview with data analysis using descriptive quantitative. The results showed that the socioeconomic conditions of families in the Cibodas Jonggol Village area showed that there were still many who were at a very poor and poor level so that there was an inability to fulfill supporting facilities and infrastructure to carry out PJJ for families.